Correlation between epidemiological data and hospital quality indicators in different regions Brazilian (Research, Society and Development, 2023)
The study aims to identify health indicators in different states of Brazil, highlighting significant disparities. This retrospective cohort study analyzed hospitalization data between 2013 and 2022 in all federal units of Brazil, correlating admission causes with hospital quality indicators using statistical analysis. The data revealed variations in hospitalization rates, length of stay, and mortality among the federal units. Admission causes such as injuries and specific diseases were predominant in various states, reflecting the need for differentiated attention in each region. The final considerations emphasize the importance of more region-specific health policies that consider the particularities of each state. Investments in disease prevention and treatment tailored to local prevalence are necessary. Furthermore, improving access to healthcare services and promoting preventive health measures are crucial for reducing the identified disparities. Policymakers in healthcare should recognize that a one-size-fits-all approach doesn't address the diverse needs of the country. Personalizing health strategies based on local realities is essential to ensure effective and equitable healthcare. The study underscores the need for a more focused and region-specific approach to enhance the healthcare system and improve the quality of life for the Brazilian population.